Effects of alpha-amylase on in vitro growth of Legionella pneumophila. - Bortner, C A (1983)
Sterile parotid saliva inhibited growth of Legionella pneumophila on solid media, and the salivary component involved in this inhibition has been shown to be amylase. Disk diffusion and well plate assays were used to study possible mechanisms for this effect. The amylolytic activity of saliva copurified with inhibitory activity, and both activities were sensitive to proteinase K digestion and heat treatment. In addition, purified alpha-amylase from several sources (bacteria, fungi, porcine pancreas, and human saliva) exhibited similar activity. Incorporation of charcoal or bovine serum albumin into media blocked inhibition by amylase. Replacement of Bacto-Agar with Noble agar (both from Difco Laboratories) prevented growth inhibition in the absence of starch. However, when corn starch was present with Noble agar, amylase-induced growth inhibition occurred. Purification of starch by washing with methanol eliminated some toxic component. The toxic component from starch could be recovered from the methanol wash and inhibited growth of L. pneumophila in the absence of amylase activity. The results suggest that toxic substances exist in media components which may be unmasked during salivary amylase digestion of starch. This effect may explain, in part, the difficulty in recovery of the organism from clinical specimens containing amylase.